Pergeseran Pelaksanaan Rebu Ngerana pada Masyarakat Karo di Desa Tanjung Sawit Kecamatan Tapung Kabupaten Kampar - Febiola Ezra Dita Ginting; Rina Susanti (Laboratory of Anthropology Department, Faculty of Humanity, Halu Oleo University, 2024)
This research aims to determine the form of shift in the implementation of rebu and the factors causing the shift in the implementation of rebu ngerana using Malinowski's Cultural Contact Theory approach. The research took place in Tanjung Sawit Village, Tapung subdistrict, Kampar district. Data collection techniques were obtained by observation, in-depth interviews, and documentation using the Miles Huberman model of qualitative data analysis. There were 8 research subjects consisting of 2 key subjects and 6 main subjects who were selected in a planned manner using purposive sampling techniques. The results of the research show that there has been a shift in the implementation of rebu ngerana, namely in the form of communication between rebu perpetrators, how to sit in the same room, sit on one mat, and there has been physical contact between rebu perpetrators which is not permitted by tradition. The factors causing the shift in the implementation of rebu ngerana are due to cultural mixing, namely the intermarriage of the Karo Batak tribe with other tribes, the influence of communication technology through social media, environmental factors which are transmigration villages, the non-implementation of customary change events, as well as situational and conditional factors.